Implementasi Total Quality Management (Tqm) Di Pondok Pesantren Darussalam Kabupaten Dharmasraya - Apriyenti Apriyenti; Ridwal Trisoni; Lita Sari Muchlis; Akhyar Hanif; Muhammad Husni Shidqi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving the quality of educational management at the Darussalam Islamic Boarding School in Dharmasraya Regency. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation studies with five key informants consisting of the foundation's leadership, the principal, the vice principal, and teachers. Data analysis was carried out through data reduction techniques, data presentation, and drawing conclusions using a thematic analysis approach. The results showed that TQM implementation was carried out through three main stages, namely participatory vision and mission-based quality planning, program implementation based on the involvement of all stakeholders, and continuous evaluation using the PDCA (Plan-Do-Check-Act) cycle. The main supporting factors include leadership commitment, religious culture, and effective organizational coordination, while inhibiting factors include limited human resources and understanding of the concept of quality. These findings indicate that the implementation of TQM based on Islamic values ​​​​is able to improve the quality of education holistically, both in academic aspects and the formation of student character.